Effectiveness of dental health education on oral hygiene among hearing impaired adolescents in India: A randomized control trial. (9th April 2019) - Hashmi, Sumbul; Mohanty, Vikrant R; Balappanavar, Aswini Y; Yadav, Vipul; Kapoor, Shivam; Rijhwani, Kavita
Abstract: Aim: To assess the effectiveness of two different methods of dental health education (DHE) for improving oral hygiene among hearing impaired adolescents in school aged 11‐20 years. Methodology and Results: A randomized double blind controlled parallel time series trial was done among 178 hearing impaired adolescents. Considering existing literature, the required sample size was found to be 82 per group, at 95% confidence interval, design effect = 1, type I error = 5%, power of study = 80%, and 20% attrition rate. Two out of five schools were randomly selected. Different methods of DHE were used, schools were coded as School A (DHE using sign language by the investigator) and School B (DHE by conventional visual method, using only posters). The mean reduction in Simplified Oral Hygiene Index (OHI‐S), Plaque Index (PI), and Gingival Index (GI) scores was 1.13 ± 0.81, 0.66 ± 0.31, and 0.58 ± 0.32, respectively, in school A. The mean reductions seen in school B was 0.52 ± 0.89 in OHI‐S, 0.44 ± 0.44 in PI, and 0.34 ± 0.32 in GI index ( P ‐value < 0.05). Conclusion: Basic training of dental professionals in sign language is both effective and feasible, and brings about greater improvement in oral hygiene status and gingival health as compared to the conventional methods of health education